The Influence of Work Environment and Work Motivation on Employee Performance at X Resort Bali - Leona, Ni Putu Leona Sukma Dewi; ⁠Ni Luh Gde Sri Sadjuni; ⁠Ni Luh Ketut Sri Sulistyawati (Jurnal Pariwisata Nusantara (JUWITA), 2024)
Purpose: This study aims to determine the influence of the work environment and work motivation on employee performance at X Resort Bali Method: The research employs a quantitative approach. The study's population consists of 150 employees, with a sample of 60 respondents selected through nonprobability sampling. Data collection was conducted by distributing questionnaires using a 5-point Likert scale to measure 30 statement items. The data analysis techniques used include classical assumption tests, multiple linear regression, determination coefficient, t-tests, and F-tests, all aided by SPSS 26 software. Result: The results of this study indicate that the work environment (X1) has a positive and significant partial effect on employee performance at X Resort Bali, as evidenced by a t-value greater than the t-table value (3.271 > 1.671) with a significance value of less than alpha (0.002 < 0.050). Motivation also has a positive and significant partial effect on employee performance, as shown by a t-value greater than the t-table value (4.103 > 1.671) with a significance value of less than alpha (0 < 0.050). The work environment and work motivation simultaneously have a significant effect on employee performance at X Resort Bali, with an F-value greater than the F-table value (51.319 > 3.16) and a significance value of less than alpha (0.000 < 0.050). The work environment and motivation contribute 64.3% to employee performance, as determined through the analysis of the determination coefficient, while the remaining 36.6% is influenced by other variables not examined in this study. Contribution: This research contributes by demonstrating that the work environment and motivation significantly improve employee performance at X Resort Bali, providing valuable insights for management to focus on these factors in efforts to enhance productivity.